Non-linear plasma protein binding of cannabidiol - Mariana Babayeva; Iva Srdanovic (BMC, 2024)
Abstract Background Cannabidiol is highly bound to plasma proteins. Changes in its protein binding can lead to altered unbound plasma concentrations and result in alteration of pharmacological activity of cannabidiol-containing medications. This research has assessed non-linearity of cannabidiol plasma protein binding and the potential effect of tizoxanide on the binding. Method Cannabidiol protein binding was evaluated by ultrafiltration technique. Human plasma was spiked with cannabidiol stock solution to produce samples of various concentrations. For interaction study potential interactant tizoxanide was added in each sample. All samples were processed through Amicon Micropartition system and analyzed by HPLC. Results The study has detected cannabidiol binding to borosilicate glass (9%) and polyethylene plastics (15%). In the interaction study the mean protein unbound fraction of cannabidiol was 0.05 (5%), indicating no binding interaction between cannabidiol and tizoxanide since cannabidiol unbound fraction without tizoxanide was also 5%. The cannabidiol fraction unbound was more than 2-fold greater at high concentrations compared to low concentrations. Conclusion a). At high concentrations cannabidiol plasma protein binding is non-linear. The non-linearity can affect elimination and medicinal effect of cannabidiol drugs. b). Borosilicate and polyethylene containers should be avoided in formulation, packing and administration of cannabidiol-containing medicines to guarantee correct doses. c). Cannabidiol medications can be co-administered with tizoxanide without caution.